Prevalence of Hepatitis E Virus in AL-Muthanna Province (Iraq) Patients - S. Muslim, Azhar; H. AL-azzawi, Raghad; S.kalief, Zainab (Iraqi Journal of Science, 2023)
Hepatitis E (HE) is an inflammation of the liver caused by hepatitis E virus(HEV) infection. Iraq is one of the Asian countries with high incidence andprevalence of hepatitis. In this paper, HE prevalence will be determined in Al-Muthanna province /Iraq. Commercially available Micro-ELISA for marker ofhepatitis E (HEV IgM, Foresight, USA) kit was used to test (270) patients for HEVIgMantibodies. Also (10) blood samples from normal healthy individuals were usedas normal control in this study. Among the (270) analyzed serum samples, a total of(72) samples (26.66 %) were found to be positive for anti-HEV IgM antibodies, andall these patients were tested for confirmatory test at central public healthlaboratories (CPHL) in Baghdad province. These patients consist of (45) femalesand (27) males were all negative for routinely screened markers of Hepatitis A,Hepatitis B and Hepatitis C. The positive sera anti-HEV IgM also were tested fortotal serum bilirubin (TSB), alanine aminotransferase (ALT), aspartateaminotransferase (AST), and alkaline phosphatase (ALP) colorimetrically. The ageranged between (4-74) years old. Highly significant differences (χ2 =10.271, p ≤0.01) appeared among age groups. This study showed that the HEV IgM is morecommon among younger age group ( 15-24), with a percentage of (41.67%). Andhigher in females (63%) than in males (37%).